Feeling Guilt and Happiness Police of The Regional Traffic Management Center (RTMC) of The East Java Regional Police to Their Families (Phenomenology Study) - Wijaya, Yunus Adi; Hariyanti, Tita; Nasution, Tina Handayani (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2021)
Guilts is the first and foremost in the form of emotional outbursts. Guilts is not a very good motivator. It is more accurate to regard guilt as an internal condition and a negative feeling. Happiness is a feeling of satisfaction, that life is as it should be and all needs have fulfilled. This study aims to find meaning in the experience of feeling guilt and happiness police of the Regional Traffic Management Center (RTMC) to their families. Qualitative interpretive phenomenology approach was conducted an in-depth interview with semistructured questions on five police officers at RTMC by purposive sampling conducted in December 2018. Based on Interpretative Phenomenological Analysis (IPA), this study found two themes namely: feeling guilty to the family and feeling happy with family. The findings obtained were that members of the police at RTMC could be free from stress while working and were able to return and get support from the family. Being able to live happily, both happy at work and happy with the family that will reflect in the calmness in their life.